Co-overexpression of the Constitutively Active Form of OsbZIP46 and ABA-Activated Protein Kinase SAPK6 Improves Drought and Temperature Stress Resistance in Rice - Chang, Yu; Nguyen, Ba Hoanh; Xie, Yongjun; Xiao, Benze; Tang, Ning; Zhu, Wenliu; Mou, Tongmin; Xiong, Lizhong (Frontiers in Plant Science, 2017)
Drought is one of the major abiotic stresses threatening rice (Oryza sativa) production worldwide. Drought resistance is controlled by multiple genes, and therefore, a multi-gene genetic engineering strategy is theoretically useful for improving drought resistance. However, the experimental evidence for such a strategy is still lacking. In this study, a few drought-responsive genes from rice were assembled by a multiple-round site-specific assembly system, and the constructs were introduced into the rice cultivar KY131 via Agrobacterium-mediated transformation. The transgenic lines of the multi-gene and corresponding single-gene constructs were pre-evaluated for drought resistance. We found that the co-overexpression of two genes, encoding a constitutively active form of a bZIP transcription factor (OsbZIP46CA1) and a protein kinase (SAPK6) involved in the abscisic acid signaling pathway, showed significantly enhanced drought resistance compared with the single-gene transgenic lines and the negative transgenic plants. Single-copy lines of this bi-gene combination (named XL22) and the corresponding single-gene lines were further evaluated for drought resistance in the field using agronomical traits. The results showed that XL22 exhibited greater yield, biomass, spikelet number, and grain number under moderate drought stress conditions. The seedling survival rate of XL22 and the single-gene overexpressors after drought stress treatment also supported the drought resistance results. Furthermore, expression profiling by RNA-Seq revealed that many genes involved in the stress response were specifically up-regulated in the drought-treated XL22 lines and some of the stress-related genes activated in CA1-OE and SAPK6-OE were distinct, which could partially explain the different performances of these lines with respect to drought resistance. In addition, the XL22 seedlings showed improved tolerance to heat and cold stresses. Our results demonstrate that the multi-gene assembly in an appropriate combination may be a promising approach in the genetic improvement of drought resistance.